Beliefs About Transitional Events: The Effect of Experience and Life-Script Consistency - Shi, Liangzi; Brown, Norman R. (Frontiers in Psychology, 2021)
The present study examined the beliefs about two types of important life transitions: transitions that are consistent with the cultural life script (Berntsen & Rubin, 2004; e.g., getting married) and transitions that diverge from it (e.g., relocating). Data were collected from two conditions: individuals in the experienced condition only responded to transitions they had experienced; individuals in the hypothetical condition provided ratings only for transitions they had not experienced. Participants rated the likelihood and typical age of occurrence, importance, transitional impact, and valence for an individualized set of condition-appropriate events. We found that script-consistent events were considered more normative and positive than script-divergent events. The two types of events, however, differed little in terms of importance or transitional impact. We conclude by arguing that although script-consistent and script-divergent transitions have much in common from a mnemonic perspective, the distinction is still warranted in the context of lifetime planning and evaluation.